2009
DOI: 10.1093/bja/aep241
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of procedural skills in anaesthesia

Abstract: A key aspect of the practice of anaesthesia is the ability to perform practical procedures efficiently and safely. Decreased working hours during training, an increasing focus on patient safety, and greater accountability have resulted in a paradigm shift in medical education. The resulting international trend towards competency-based training demands robust methods of evaluation of all domains of learning. The assessment of procedural skills in anaesthesia is poor compared with other domains of learning and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
29

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(191 citation statements)
references
References 93 publications
3
156
0
29
Order By: Relevance
“…5 Owing to the dependency of patients' outcomes on a surgeon's technical skills, research into this area has been pioneered in surgery. 6 Several assessment tools have now been developed and validated for use on surgical trainees outside the operating room.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…5 Owing to the dependency of patients' outcomes on a surgeon's technical skills, research into this area has been pioneered in surgery. 6 Several assessment tools have now been developed and validated for use on surgical trainees outside the operating room.…”
Section: Résumémentioning
confidence: 99%
“…5,[27][28][29][30] In one study, cusum was used to determine the amount of training required to achieve competency in spinal ultrasound. 27 The conclusion was that 20 attempts and a coaching session were not sufficient to teach the relevant skills, and that this should inform the planning of future educational sessions and workshops.…”
Section: Ultrasound Skillsmentioning
confidence: 99%
“…13,14 Combining various simulation modalities (e.g., standardized patients, task trainers, electromechanical mannequins) allows for a broader modelling of practice situations, making it possible to measure the multiple abilities or competencies required in anesthesia practice. [15][16][17][18] Nevertheless, while some very innovative scenario designs have been forwarded, there remains the need to ensure that student, resident, or practitioner assessments generate resulting scores or decisions that are meaningful and accurate. The qualities of ''good'' assessments are discussed in the next section.…”
Section: Types Of Assessmentsmentioning
confidence: 99%
“…35,36 As mentioned previously, the long history of simulation in anesthesiology 37 coupled with advances in technology has effectively broadened the potential assessment domain for the specialty. 18 This affiliation has allowed for the measurement of both procedural 17 and non-technical skills such as communication, situational awareness, teamwork, and professionalism. 38 A thorough review of the use of simulation for assessment in anesthesiology can be found elsewhere.…”
Section: Patient Carementioning
confidence: 99%
See 1 more Smart Citation